Two Long-Acting Antipsychotics in a Patient with Treatment-Resistant Schizophrenia: A Case Report - Salvatore Cipolla; Flora Delli Carpini; Pierluigi Catapano; Valeria De Santis; Antonio Volpicelli; Francesco Perris; Francesco Catapano (Clinics and Practice)
Treatment-resistant schizophrenia (TRS) poses significant therapeutic challenges due to persistent symptoms, poor adherence, and high relapse rates. Long-acting injectable (LAI) antipsychotics offer a promising approach, yet limited evidence exists regarding the combination of two LAI formulations. We report the case of a 62-year-old woman with TRS, characterized by recurrent hospitalizations and inadequate responses to oral and monotherapy treatments. During her latest hospitalization, she received alternating intramuscular administrations of haloperidol decanoate (100 mg/28 days) and aripiprazole (400 mg/28 days). The dual LAI strategy resulted in a marked improvement in psychotic symptoms, functional recovery, and treatment adherence, with no reported side effects. This case highlights the potential benefits of dual LAI therapy in managing TRS, particularly in patients with non-adherence to oral medications or limited response to standard treatments. Additional studies are required to evaluate the long-term effectiveness and safety of this innovative therapeutic approach.